CORRELATIONS BETWEEN SUCCESSFUL THERAPY AND ANXIETY LEVEL OF POST OPERATIVE GLAUCOMA PATIENTS - Singgih Pratama; Arief Wildan; Riski Prihatningtias; Fifin Luthfia Rahmi (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background : Glaucoma is a disease that can cause damage to the optic nerve. High intraocular pressure is a major risk factor for glaucoma. The main goal of treating glaucoma is to control the disease progression by reducing intraocular pressure to the normal range or in accordance with the target pressure, and unsuccessful treatment can lead to anxiety. Aims : Identifying the correlation between therapeutic success and anxiety levels in post-operative glaucoma patients. Methods : This research used observational analytic method with a cross-sectional design. A total of 34 post-operative glaucoma patients were collected by consecutive sampling at the Eye Outpatient Installation of Dr. Kariadi Hospital Semarang. The anxiety level was assessed using the Taylor Manifest Anxiety Scale (TMAS) questionnaire. Data analysis in the study used the Contingency Coefficient test. Results : A total of 34 glaucoma patients consisted of 17 patients who successfully achieved the target pressure and 17 patients who failed to achieve the target pressure. There was a significant correlation between the success of glaucoma therapy with anxiety levels (p = 0.008) and there was a weak relationship between the two variables (r = 0.471). Conclusion : There is a correlation between therapeutic success and anxiety levels in post-operative glaucoma patients.